Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18203/2394-6040.ijcmph20182652
|View full text |Cite
|
Sign up to set email alerts
|

Stress among medical students of a tertiary health care centre in tribal area of central India: a prospective observational study

Abstract: Background: Medical education has been reported to be one of the most stressful academic curricula worldwide, negatively affecting the physical and mental health of medical students. A medical student can be stressed due to different reasons or stressors such as the academic, financial problem, health problem or loss of close family member or friend, etc. It is the person’s ability to face the everyday challenges which will determine whether he/she will be stressed or not. This stress manifests itself in a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…Both values are lower than other studies. [8][9][10] Our study showed mean GRS of 1.82 ± 0.77, which is higher than other studies. 8,10 Study done in Rural medical college, Ahmednagar, Maharashtra compared the levels of different stressors in males and females and showed that both genders have moderate stress in all the stressors.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Both values are lower than other studies. [8][9][10] Our study showed mean GRS of 1.82 ± 0.77, which is higher than other studies. 8,10 Study done in Rural medical college, Ahmednagar, Maharashtra compared the levels of different stressors in males and females and showed that both genders have moderate stress in all the stressors.…”
Section: Discussioncontrasting
confidence: 71%
“…More ARS in our study is in accordance with other studies. [8][9][10][11] Our study included students of 1 st MBBS only. Debashree et al 8 study also included 1 st year students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation